TELAAH TERHADAP BINDING AND LOOSING PRAYER: SEJAUH MANA OTORITAS ORANG PERCAYA DALAM PEPERANGAN ROHANI? A STUDY OF AGAINST BINDING AND LOOSING PRAYER: AS FAR AS THE AUTHORITY OF BELIEVERS IN SPIRITUAL WARNING? - Murni Hermawaty Sitanggang (Jurnal Teologi Amreta (ISSN: 2599-3100))
ABSTRACT This article discusses the problem about binding and loosing prayer or deliverance prayer in its popular term. For the proponent, this concept, binding and loosing prayer is considered the important part in spiritual warfare that had to be practiced every day. Whereas the group who refuse assume this kind of prayer is arisen more from experience than the thorough biblical exegesis. This article will discuss the controversy about this binding and loose prayer and then examine the biblical verses that use to be basic for this prayer for answer the main question, to what extent the authority that believer has in spiritual warfare. Abstrak Tulisan ini membahas problematika seputar doa mengikat dan melepaskan (binding and loosing prayer) atau yang juga populer dengan sebutan doa pelepasan. Bagi kalangan yang menganjurkannya, doa ini dianggap merupakan bagian penting dalam peperangan rohani yang harus dilakukan orang percaya setiap hari. Sedangkan bagi mereka yang menolaknya, doa ini lebih didasarkan pada pengalaman daripada penafsiran yang benar terhadap Alkitab. Tulisan ini akan membahas pro dan kontra tersebut kemudian menelaah ayat-ayat Alkitab yang biasanya dipakai untuk membenarkan praktik ini untuk kemudian menjawab pertanyaan utama: sejauh mana otoritas orang percaya dalam peperangan rohani.